The Attractiveness of a City-Centre Shopping Environment: Older Consumers’ Perspective - Anna-Maija Kohijoki; Katri Koistinen (Cogitatio, 2022)
Older consumers represent an increasingly significant customer segment for city-centre retailers. However, many intraurban centres are struggling to maintain an attractive shopping environment. This article focuses on older consumers’ (Finns, aged 64+) perceptions of the city centre with an emphasis on design and ambient elements in the external shopping environment. Using the focus-group research method, the aim is to identify what kind of elements these are and how they constitute an attractive city-centre shopping environment for older consumers. Findings from a qualitative content analysis show that an attractive city-centre shopping environment provides convenience and safety when moving around and running errands, functional and aesthetic lighting to cope with shopping, proper furnishings regarding places to rest, harmonious building architecture integrated with refreshing urban nature, and the cleanliness of the streetscape. Findings indicate that a city-centre shopping environment offers more to older consumers than a context of satisfying consumption needs. City shopping gives a reason to go outdoors and maintain social contacts. The study has implications for creating an age-friendly city centre, the shopping environment which supports older consumers’ active and independent lives.